Quasi β-power increasing sequences - H. Bor; L. Debnath (International Journal of Mathematics and Mathematical Sciences)
We prove a theorem of Mazhar (1999) on |N¯,pn|k summability factors under weaker conditions by using a quasi β-power increasing sequence instead of an almost increasing sequence.